An Islamic perspectives on public art : a case study of Laman Seni 7,Shah Alam - Che Man, Shaibatul Islamiah; Mansor, Mazlina; Zakariya, Khalilah (2014)
This paper aims to examine the elements of public art from the Islamic perspectives in the aspect of social values. The evolution of public art and its roles have been central in the discussion of arts in public spaces primarily from the Western perspectives. Numerous literatures and studies have acknowledged the values of public art from social and cultural aspects. However, studies on the meaning and values of public art from religious perspectives are scarce. Thus, this paper illustrates to impart a different view of existing public art in Malaysia, which came in a more contemporary form than the traditional Islamic art. As such, this paper explains the applications of art elements that has been portrayed along back alleys in Shah Alam. Seeing public art is the part of urban landscape elements, it has also potential to evoke spiritual values and remind people about the Creator and His creations, and act as an informal platform for good values and knowledge to be disseminated. The study is conducted through site observation method and assessment from site inventory using three main topics: Elements of public art , Social values, and meaning from Islamic perspectives. The observations were supported by photos. From the assessment done, contemporary representation of public art also able to offer diverse noble values in line with the values of Islam. Attributes that may be infused into the creation of public art are identified to further guide the possible directions of Islamic public art in the future.